(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
According to the results of long-term monitoring (1974–2013) on permanent sample plots of the Institute of Ecology of the Carpathians National Academy of Sciences of Ukraine, in an ecosystem dominated by Juniperus communis, patterns of self-recovery (regeneration) of the population structure Soldanella hungarica after local destruction of herbaceous vegetation were examined. It was established experimentally that such small-scale effects do not create the preconditions for the further destabilization of the population. But they initiate the mobilization of reserve S.hungarica population in adjacent areas. The relationship of individual responses and group effects in the processes of self-recovery is shown. It is concluded about imperative importance of vitality of the local population regeneration of S.hungarica. Though it is still not fully predictable process that has been continuing for several decades.